Thoracic endometriosis syndrome diagnosed by dry thoracoscopy: Novel diagnostic method for a rare disease - Parul Sharma; Saurabh Karmakar; Abdul Raouf Wani; Vinay Venugopal; Debapriyo Maji (Lung India)
Endometriosis is an ectopic implantation of uterine tissue and can affect the thoracic cavity, resulting in Thoracic Endometriosis Syndrome (TES). TES is rare and presents with catamenial pneumothorax, haemothorax, and hemoptysis, often coinciding with menstruation. We report a case of a 46-year-old female with a decade-long history of hemoptysis and periodic chest pain associated with her menstrual cycle. High-resolution CT scans revealed persistent pneumothorax and pleural nodules. A dry thoracoscopy was performed, and biopsies confirmed the diagnosis of TES through histopathology and immunohistochemistry. This case highlights the importance of considering TES in women with cyclic respiratory symptoms and demonstrates the diagnostic value of dry thoracoscopy in benign conditions of the pleura. Raising awareness among clinicians is crucial for timely diagnosis and management of TES, reducing patient morbidity.